Determination of GT-transition Strengths in \(A=34\) Isobars Using Charge Exchange \((^3He,t)\) Reaction - Khai, Nguyen Tuan; Linh, Bui Duy; Thiep, Tran Duc; Fujita, Y.; Adachi, T; Fujita, H.; Tamii, A. (Communications in Physics, 2012)
Under the assumption that isospin \(T\) is a good quantum number, mirror transitions \(T_z = +1 → 0\) and \(T_z = -1 → 0\) were studied in \(A = 34\) isobars, where \(T_z\) is \(z\) component of iospin \(T\) and is defined by \(T_z = (N-Z)/2\). With a high energy resolution of 35 keV in \(^34\)S\((^3He,t)^34\)Cl reaction measurement at \(0^°\) scattering angle and at an incident energy of 140 MeV/nucleon, strengths of Fermi and Gamow-Teller (GT) transitions from the \(J^π = 0^ + \), \(T_z = +1\) ground state of \(^34\)S to the \(J^π = 1^+ \), \(T_z = 0\) excited states in \(^34\)Cl were determined up to excitation energy \((E_x)\) of \(7.08\) MeV. The corresponding isospin-symmetric transitions connecting \(T_z = -1\) and \(T_z = 0\) states can be studied in the \(^34\)Ar \(β ^ + \) decay. The strengths of the \((GT)_± \) transitions were compared up to the excitation energy of 3.1 MeV. A good agreement was observed for two strong transitions to \(2.580\) MeV and \(3.129\) MeV states, while a disagreement about \(45%\) was observed for a weaker transition to \(0.666\) MeV low-lying state.